2022
DOI: 10.3390/ijerph19063616
|View full text |Cite
|
Sign up to set email alerts
|

How Are Non-Medical Settlement Service Organizations Supporting Access to Healthcare and Mental Health Services for Immigrants: A Scoping Review

Abstract: Following resettlement in high-income countries, many immigrants and refugees experience barriers to accessing primary healthcare. Local non-medical settlement organizations, such as the Local Immigration Partnerships in Canada, that support immigrant integration, may also support access to mental health and healthcare services for immigrant populations. This scoping review aims to identify and map the types and characteristics of approaches and interventions that immigrant settlement organizations undertake t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Nineteen systematic reviews (Aggarwal et al 2016, Anderson et al 2015, Arundell et al 2021, Bhui et al 2015, Castellanos et al 2019, Degnan et al 2018, Ellis et al 2022, Giebel et al 2015, Hernandez Robles et al 2018, Interian et al 2013, Iqbal et al 2022, Lee-Tauler et al 2018, Li et al 2023, McFadden et al 2018, Moffat et al 2009, Moore 2018, Sass et al 2009, Soltan et al 2022, Taylor et al 2023), seven scoping reviews (Apers et al 2023, Handtke et al 2019, Hynie et al 2023, Place et al 2021, Ratnayake et al 2022, Rogers et al 2020, Thomson et al 2015), one mapping review 3 (Arundell et al 2020), three narrative review (Griner and Smith et al 2006, Kalibatseva and Leong 2014, Mukadam et al 2013), two overviews of reviews (Rathod et al 2018, Uphoff et al 2020), one scoping review of reviews (Chakanyuka et al 2022) and four protocols (Aslam et al 2018, Stockwell and Roche 2022, Wang and Kim 2019, Wood et al 2023) were identified across the literature searches of bibliographic databases. The detail from each of these reviews is reported in Table 2.…”
Section: Research Question(s)mentioning
confidence: 99%
See 3 more Smart Citations
“…Nineteen systematic reviews (Aggarwal et al 2016, Anderson et al 2015, Arundell et al 2021, Bhui et al 2015, Castellanos et al 2019, Degnan et al 2018, Ellis et al 2022, Giebel et al 2015, Hernandez Robles et al 2018, Interian et al 2013, Iqbal et al 2022, Lee-Tauler et al 2018, Li et al 2023, McFadden et al 2018, Moffat et al 2009, Moore 2018, Sass et al 2009, Soltan et al 2022, Taylor et al 2023), seven scoping reviews (Apers et al 2023, Handtke et al 2019, Hynie et al 2023, Place et al 2021, Ratnayake et al 2022, Rogers et al 2020, Thomson et al 2015), one mapping review 3 (Arundell et al 2020), three narrative review (Griner and Smith et al 2006, Kalibatseva and Leong 2014, Mukadam et al 2013), two overviews of reviews (Rathod et al 2018, Uphoff et al 2020), one scoping review of reviews (Chakanyuka et al 2022) and four protocols (Aslam et al 2018, Stockwell and Roche 2022, Wang and Kim 2019, Wood et al 2023) were identified across the literature searches of bibliographic databases. The detail from each of these reviews is reported in Table 2.…”
Section: Research Question(s)mentioning
confidence: 99%
“…Findings from the scoping review by Ratnayake et al (2022) showed that local non-medical immigrant settlement organisations had established approaches and interventions to support immigrants access to primary healthcare services , with most studies showing that mental health support was an important component. These included connecting to healthcare services and / or collaborating with health sector institutions; providing health promotion programs; undertaking community capacity-building and policy advocacy activities and providing on the ground assistance.…”
Section: Research Question(s)mentioning
confidence: 99%
See 2 more Smart Citations